(untitled) (ARQUISUR Revista, 2015)
The Kunsthall, is a manifesto building in which virtually all the conceptual elements of the architecture of OMA are present, questioning the program, the type, the structure, the detailing and technique. A non-hierarchical space, without center, a-typological, where public-private, open-closed melt and never appear in pure form. A hybrid program, the result of understanding reality as a complex fact, seeking to contain the unstable and to adapt to constant change. A structure of seemingly chaotic appearance, compared to the homogeneity of a grid, the result of simulation calculation methods that incorporate the complexity of reality, resulting in a different rationality, which is not simple, nor abstract, nor homogeneous. A look of technology from the architectural thinking, where structure and infrastructure become central elements and spatial triggers, by working with specialists early in the process. A selective detailing control strategy, with a programmatic intention of creating a crisis of the principles established by the architectural culture, questioning the value of detail and the technique. So, Koolhaas, is seeking the pure concept and building a different rationality that only apparently contains irrational in its essence aspects.